Avian response to conservation buffers in agricultural landscapes during winter - Kristine O. Evans; L. Wes Burger Jr.; Samuel K. Riffell; Mark D. Smith; Daniel J. Twedt; R. Randy Wilson; Shawchyi Vorisek; Catherine Rideout; Kate Heyden (Wildlife Society Bulletin)
ABSTRACT Native herbaceous vegetation cover along row‐crop field edges (i.e., field buffers) increases breeding densities of many bird species. However, the effect of field buffers on bird species during the non‐breeding season is less understood. We compared density, avian richness, and avian conservation value on row‐crop fields containing buffers strategically designed for wildlife versus fields without buffers in 3 southeastern U.S. states during winter 2007 and 2008. Fields with buffers were enrolled in U.S. Department of Agriculture, Conservation Reserve Program practice Habitat Buffers for Upland Birds (CP33), which targets restoration of northern bobwhite (Colinus virginianus) and other upland bird species. Overall species richness did not differ on fields with buffers versus fields without buffers in 2007, but was 29% greater on fields with buffers in 2008. Swamp sparrows (Melospiza georgiana), song sparrows (M. melodia), field sparrows (Spizella pusilla), and red‐bellied woodpeckers (Melanerpes carolinus) had greater densities on fields with buffers compared with fields without buffers. Increasing field‐buffer width did not result in greater bird densities. Our results suggest a small change in primary land use (≈7%) produced a disproportionate population response by some grassland‐dependent and woodland bird species during winter. Because field buffers provide a direct source of winter food and cover resources, they may be a pragmatic means to provide critical non‐breeding habitat with little alteration of existing agricultural systems. © 2014 The Wildlife Society.